THE IMPORTANCE OF IMPROVING LEXICAL COMPETENCE OF MEDICAL STUDENTS IN THE EFL CLASSROOM - Saparbaeva Saltanat Omirbaevna (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The article describes the importance of improving lexical competence of medical students in the English as a foreign language classroom. The article deals with some issues related to teaching foreign language vocabulary in the medical field at a medical university. In the paper, descriptive and comparative methods analyses have been used.